Edentulism, loss of functional dentition and oral mucosal lesions in community-dwelling older people: Edentulismo, perda de dentição functional e lesões de mucosa bucal em idosos da comunidade - Rodrigues Junior, Sinval Adalberto; da Silva Corralo, Vanessa; Lasta, Rafaela; Gassen Kellermann, Michele; Marcon, Scheila; Antônio de Sá, Clodoaldo (Revista FisiSenectus, 2026)
Introduction: Oral health problems may affect the systemic health of older people, eventually contributing to frailty. Aim: to determine risk factors for edentulism, loss of functional dentition and oral mucosal lesions in community-dwelling elderly. Methodology: This cross-sectional study was conducted in an older people care program in Southern Brazil. Sociodemographic and socioeconomic variables were collected by questionnaires, and the clinical oral condition of the participants was assessed by oral clinical examination. Edentulism and loss of functional dentition were determined based on the count of teeth, while the oral lesions were identified clinically. Bivariate and multivariate logistic regression models were used to determine the odds of edentulism, loss of functional dentition and oral lesions. Results: 148 elders participated of the study, with a mean age of 69.5 ± 6.3 years. Being female increased the odds of being edentulous (OR=2.247; 95%CI=1.076-4.693) and of lacking functional dentition (OR=3.947; 95%CI=1.789-8.705), along with being older than 72 years as compared to people with 66 years of less (ORedentulism=2.574; 95%CI=1.033-6.415 and ORfunctional_dent=4.961; 95%CI=1.700-14.482). People who did not wear upper full denture had a OR=0.175 (95%CI=0.072-0.426) of presenting oral mucosal lesions. Conclusion: Being female and older significantly increases the odds of being edentulous or lacking functional dentition. Besides, using upper full denture increases the odds of presenting oral mucosal lesions.